Study of ambipolar and linearity behavior of the misaligned double gate-drain dopant-free Nano-TFET: Design and performance enhancement. (March 2023) - Shekhar, Deep; Raman, Ashish
Abstract: Work done in this article demonstrates the charge plasma based misaligned double gate-drain doping less tunnel field effect transistor. Designed devices such as perfectly aligned and misaligned, both are optimized by considering the secondary drain in order to investigate ambipolar and linearity behavior. As the work function of secondary drain increases reduction in the ambipolar current is observed with a little degradation in ON state current. It presents a tradeoff between ambipolar current and ON current hence suitable work function of secondary drain is necessary for the proper working of the device. Analog parameters such as ON current, ambipolar current, subthreshold slope, ON to OFF current ratio, ON current to ambipolar current ratio, threshold voltage are analyzed with respect to secondary drain. In order to investigate the device performance for low voltage and low noise applications various linearity parameters such as higher order transconductances, higher order harmonic distortions, higher order intermodulation point and transconductance gain factor have also been demonstrated all the designed structures. The values of ON current for perfectly aligned, underlap, overlap and both gate misaligned structure at 4.2eV of secondary drain work function is 52 μA, 30 μA, 18 μA and 12 μA respectively. And ambipolar current for perfectly aligned, underlap, overlap and both gate misaligned structure at 4.2eV of secondary drain work function is 3 pA, 23 pA, 247 pA and 705 pA respectively.